ANALISIS PENGARUH ONLINE CUSTOMER REVIEW TERHADAP MINAT BELI KONSUMEN PADA PRODUK KOSMETIK (Studi Kasus pada Pengguna Famaledaily Indonesia) - Syah, Muhammad Ariq; Indriani, Farida (Faculty of Economics and Business Diponegoro University, 2020)
This research aims to analyze the influence of online customer review towards consumer purchase intention of cosmetic in Indonesia. To achieve the research objectives, author conducted a case study on one of the largest review platforms in Indonesia, namely Femaledaily.There are four independent variables (review quality, review quantity, review valence, and credibility source) to examine the effect of online consumer review toward purchase intentionThe sampling method used on this research is non-probability sampling with purposive sampling technique. Samples collected from 100 respondents in Indonesia who had read a review through the application or the Femaledaily website.The results showed that the review quality, review quantity, and review valence has a positive and significant effect on purchase intention for cosmetics products. While the review valence does not have a significant influence on purchase intention. By knowing the results of this research, marketers are expected to consider online customer reviews as marketing strategies that can be used to increase company sales.